2021
DOI: 10.1029/2020pa004206
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Carbonate Dissolution Associated With Deglacial Dysoxic Events in the Subpolar North Pacific

Abstract: Introduction Oxygen Minimum and Carbonate Maximum Zones in the PacificOxygen minimum zones (OMZs) are regions at intermediate ocean depths with low dissolved oxygen content, the extent of which vary over time with ocean circulation, nutrient availability, and climate (Deutsch et al., 2011;Helly & Levin, 2004;Keeling et al., 2010). These zones are forecast to expand and intensify with ongoing global climate change driven by rising anthropogenic CO 2 (Keeling et al., 2010;Long et al., 2016;Stramma et al., 2008).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 105 publications
0
1
0
Order By: Relevance
“…Sediment CaCO3 may be affected by dissolution. A previous study found evidence of enhanced dissolution at the intermediate-depth site during the severe deoxygenation intervals but not during the mild deoxygenation intervals 68 . Carbonate dissolution is expected to be stronger at the abyssal site, and thus the increase in calcareous productivity indicated here is likely underestimated.…”
Section: Productivity Proxiesmentioning
confidence: 83%
“…Sediment CaCO3 may be affected by dissolution. A previous study found evidence of enhanced dissolution at the intermediate-depth site during the severe deoxygenation intervals but not during the mild deoxygenation intervals 68 . Carbonate dissolution is expected to be stronger at the abyssal site, and thus the increase in calcareous productivity indicated here is likely underestimated.…”
Section: Productivity Proxiesmentioning
confidence: 83%